Pengaruh Struktur Kepemilikan Keluarga terhadap Kinerja Perusahaan pada Sektor Industri Dasar dan Kimia - Carolina Limantoro; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
Theoretically firm performance of family ownership structures has many advantages, however there was inconsistency in previous research results on the affect of family ownership structures on firm performance. This study aimed to prove the affect of family ownership structure on firm performance. Family ownership structure is measured by using a minimum shareholding of 10% or a family member has a position in the firm managerial. Firm performance were measured by Return on Assets (ROA). The control variables used Good Corporate Governance (GCG) and Leverage. The sample in research conducted on basic industry and chemicals sectors consisted of 56 go public firms and listed in Indonesia Stock Exchange (BEI) in period 2010-2015 with a sample of 280 observations. The results showed that family ownership structure had significant positive affect on firm performance. While the GCG had significant negative affect on firm performance, and leverage had significant negative affect to firm performance.